Aspectos semântico-pragmáticos da enunciação radiofônica - Máximo, Willian Corrêa (2009)
Colloquial, immediate, with great penetration and low cost, the “almost” interaction of the radio has continued for more than one hundred years calling the attention upon the society, particularly in local cultures. This electronic way of instantaneous language has been very renowned this Century, with high indexes of audience in Tubarão-SC. The City where living more than 90 thousand people is the cradle of Sociedade Rádio Tubá Ltda., established since almost 60 years old, being one of the oldest in Santa Catarina is part of the Catholic Radio Broadcast station. The present study describes the characteristics of the enunciating act from speak in news and interviews presented by Show do Rádio program from the station, aimed to observe some peculiarities of the language: approaching and distancing with the sources, discursive strategies, by the light of Journalism and the language theories. From the newsworthiness criteria – postulated in the Newsmaking theory – the news presented in the Show do Rádio program relates past happenings with the logic of selection, including and excluding facts based on personal, institutional and cultural orientations. On interviews, the program presents a try of interaction from the absence of production and guidance of agendas, betting on the spontaneity of interviewer and interviewed as a condition to a possible dialogue. In its semantic-pragmatic aspects, Journalism on the radio manifests itself while social construction on the science of language field when spreading and mediating mutually the happenings between the sender and receiver, at the same time when it produces meanings, re-meaning them and/or mystifying them – own consequence of language – legitimating general assents in a “game” of words and sense creation and organization